Ceftaroline fosamil versus ceftriaxone for the treatment of Asian patients with community-acquired pneumonia: a randomised, controlled, double-blind, phase 3, non-inferiority with nested superiority trial. Issue 2 (February 2015) - Zhong, Nan Shan; Sun, Tieying; Zhuo, Chao; D'Souza, George; Lee, Sang Haak; Lan, Nguyen Huu; Chiang, Chi-Huei; Wilson, David; Sun, Fang; Iaconis, Joseph; Melnick, David
Summary: Background: Ceftriaxone with or without a macrolide antibiotic is a recommended treatment for patients with community-acquired pneumonia requiring hospital admission and intravenous antibiotic treatment. We aimed to assess the efficacy and safety of ceftaroline fosamil compared with ceftriaxone in the treatment of Asian patients admitted to hospital with community-acquired pneumonia. Methods: In this international, randomised, controlled, double-blind, phase 3, non-inferiority with nested superiority trial, adult Asian patients with Pneumonia Outcomes Research Team (PORT) risk class III–IV acute community-acquired pneumonia were randomly assigned (1:1) to receive intravenous ceftaroline fosamil (600 mg every 12 h) or ceftriaxone (2 g every 24 h) for 5–7 days. Patients were randomly assigned via centralised telephone and web-based system; patients and treating clinicians were masked to treatment allocation. Investigators who did study assessments remained masked to treatment allocation until completion of the study. The primary endpoint was clinical cure at the test-of-cure visit (8–15 days after last dose of study drug) in the clinically evaluable population. Non-inferiority of ceftaroline fosamil was defined as a lower limit of the two-sided 95% CI for the difference in the proportion of patients clinically cured of −10% or higher; if non-inferiority was achieved, superiority was to be concluded if the lower limit of the 95% CI was greater than 0%. This trial is registered withClinicalTrials.gov, numberNCT01371838 . Findings: Between Dec 13, 2011, and April 26, 2013, 847 patients were enrolled at 64 centres in China, India, South Korea, Taiwan, and Vietnam, of whom 771 were randomly assigned and 764 received study treatment. In the clinically evaluable population (n=498) 217 (84%) of 258 patients in the ceftaroline fosamil group and 178 (74%) of 240 patients in the ceftriaxone group were clinically cured at the test-of-cure visit (difference 9·9%, 95% CI 2·8–17·1). The superiority of ceftaroline fosamil was consistent across all preplanned patient subgroup analyses (split by age 65 years, age 75 years, sex, PORT risk class, and previous antibiotic use) apart from patients younger than 65 years. The frequency of adverse events was similar between treatment groups and the safety results for ceftaroline fosamil were consistent with the cephalosporin class and previous clinical trial data. Interpretation: Ceftaroline fosamil 600 mg given every 12 h was superior to ceftriaxone 2 g given every 24 h for the treatment of Asian patients with PORT III–IV community-acquired pneumonia. These data suggest that ceftaroline fosamil should be regarded as an alternative to ceftriaxone in empirical treatment regimens for this patient population. Funding: AstraZeneca.